Mechanical Behavior of Plastic Strips-Reinforced Expansive Soils Stabilized with Waste Marble Dust - Shelema Amena; Worku Firomsa Kabeta (Advances in Civil Engineering)
Expansive soil needs to undergo treatment to be used as safe foundation soil for roads and buildings. From an environmental conservation and economical point of view, the usage of agricultural and industrial wastes is the best option. In this study, the effects of utilizing plastic waste and marble waste dust on the engineering properties of expansive soils were examined. Various laboratory tests were carried out on sampled expansive soil by adding 10, 15, and 20% of marble and 0.25, 0.5, and 0.75% of 5 × 8 mm2 plastic strips. The laboratory test results showed that there are good enhancements on strength parameters due to the addition of marble dust and plastic strips. With an increase in percentages of marble dust and plastic strips, California Bearing Ratio (CBR) values rise. With the addition of marble dust, unconfined compressive strength (UCS) values increase linearly, while they increase only up to 0.5% with the addition of plastic strips. As the proportions of marble dust and plastic strips increase, the soil’s free swell and CBR swell are decreased significantly. This shows that environmental pollution waste marble dust and plastic strips can be utilized to strengthen the weak subgrade soil and minimize its swelling properties. Therefore, this study found out that the expansive soil treated with polyethylene terephthalate (PET) plastic and marble dust can be used as a subgrade material since it fulfills the minimum requirement needed by standards.